The Arabic's Significant Role In The Understanding Of Islamic Law - Ihsan Sa'dudin; Jefik Zulfikar Hafizd; Eka Safitri (Makassar State University, 2022)
Abstract. This study intends to examine the role of Arabic in comprehending Islamic law. This research was conducted to provide an overview of Arabic for observers of Islamic law, focusing on the elements of nahwu, shorof, balaghah, and mantiq. This is because the Quran and Hadith, the primary sources of Islamic law, are written in Arabic. This research was a literature study using the descriptive analysis method to examine the importance of mastering Arabic in the study of Islamic law. Sources of research data were obtained from various references that include books, journals, and other references related to the research theme. The result showed that Arabic is essential for comprehending the Al-Quran and Hadith as the primary sources of Islamic law. The Arabic language used by the Qur'an was much higher than the Arabic language that developed in the community. In Arab society during the Jahiliyah era, the Arabic language had reached its qimmah (glory) and was mature in terms of its grammar, vocabularies, uslub (language style), and balaghah. Al-Qur'an and hadith cannot be separated from Arabic, hence the accuracy with which both are read and comprehended will determine whether or not Islamic law is established.Keywords: Arabic, Al-Qur’an, Islamic Law, Spirit of Islam